Characterization of Yttria Stabilized Zirconia thermal spray coatings by use of NMR Cryoporometry and SEM - Cronquist, Charlotte (My University, 2019)
Thermal Barrier Coatings (TBC) are of major importance in high temperature applications such as turbines, where temperatures above 1000°C are reached. The TBCs protect the base metal (i.e. the actual turbine) by providing a layer of material with low thermal conductivity and heat-transfer. Ceramic materials such as Yttria Stabilized Zirconia (YSZ) are suitable as TBC materials as they provide for heat resistant behavior. By tailoring the microstructure, the desired thermal conductivity and toughness can be achieved. Suspension Plasma Spraying (SPS) provides for this by forming a columnar microstructure containing both nano- and microporosity. NMR Cryoporometry (NMRC) is a known method used to investigate pore size distribution and pore shape in organic materials. NMRC has also shown to be a promising analysis technique for ceramic material. This work aimed to investigate YSZ coatings produced by SPS with water as probe liquid. This allowed the measurement of pores of a few nanometers in diameter. Special care was taken to improve the sample preparation in order to achieve a suitable signal-to-noise ratio in the NMR-signal. To capture the changes in the YSZ coatings during the sintering at high temperatures in a potential application (some pores will open up while others will close), as-sprayed and heat-treated samples were investigated, and pore size and shape were compared. The results are compared with previous measurements performed on the same material using Mercury Intrusion Porosimetry and Image Analysis as well as NMR Cryoporometry using another probe liquid (OMCTS).
Keywords: Suspension Plasma Spraying; Yttria Stabilized Zirconia; nanoporosity; NMR Cryoporometry